Diabetic Ketoacidosis and Hyperosmolar Hyperglycemic State: Diagnosis and Management in Emergency Condition – A Literature Review - Wongso Prawiro, Aurellia; Rofilah, Alita Khainur; Putri, Imey Pinasty Harianto; Praditna, Lalu M. Ardi; Hasanah, Mielosita; Husodo, Dewi Puspitorini (Jurnal Biologi Tropis, 2025)
Diabetic ketoacidosis (DKA) commonly occurs in type 1 diabetes due to absolute insulin deficiency, whereas HHS typically develops in type 2 diabetes with relative insulin deficiency. These distinct mechanisms result in different clinical and laboratory profiles. This review aims to compare the pathogenesis, clinical features, and current management of DKA and HHS. This study employed a narrative literature review design. Articles were retrieved from PubMed, Scopus, and Google Scholar using the keywords “diabetic ketoacidosis,” “hyperosmolar hyperglycemic state,” “diabetes mellitus,” and “complications,” covering publications from 2015 to 2025. A descriptive analysis was performed to highlight epidemiology, pathogenesis, clinical manifestations, and emergency management principles. The review indicates that DKA is more frequent and associated with lower mortality when promptly recognized and treated. In contrast, HHS is less common but carries a higher mortality rate, mainly due to severe dehydration, insidious onset, and delayed diagnosis. Management principles for both conditions are similar, including fluid resuscitation, insulin therapy, electrolyte correction, and treatment of precipitating factors. A comprehensive understanding of the differences between DKA and HHS is essential to support early diagnosis, guide appropriate treatment, and reduce mortality.